Antimicrobial Resistance of Major Bacterial Pathogens from Dairy Cows with High Somatic Cell Count and Clinical Mastitis - Reta D. Abdi; Barbara E. Gillespie; Susan Ivey; Gina M. Pighetti; Raul A. Almeida; Oudessa Kerro Dego (Animals, 2021)
Mastitis is the most prevalent and economically important disease caused by different etiological agents, which leads to increased somatic cell count (SCC) and low milk quality. Treating mastitis cases with antimicrobials is essential to reduce SCC and improve milk quality. Non-prudent use of antimicrobials in dairy farms increased the development of antimicrobial resistant bacteria. This study’s objectives were (1) to isolate and identify etiological agents of mastitis and (2) to determine antimicrobial resistance profiles of bacterial isolates. A total of 174 quarter milk samples from 151 cows with high SCC and clinical mastitis from 34 dairy farms in Tennessee, Kentucky, and Mississippi were collected. Bacterial causative agents were determined by bacteriological and biochemical tests. The antimicrobial resistance of bacterial isolates against 10 commonly used antimicrobials was tested. A total of 193 bacteria consisting of six bacterial species, which include Staphylococcus aureus, Streptococcus uberis, Streptococcus dysgalactiae, Escherichia coli, Klebsiella oxytoca and Klebsiella pneumoniae were isolated. Staphylococcus aureus was the predominant isolate followed by Strep. spp., E. coli, and Klebsiella spp. Results of this study showed that Gram-negatives (E. coli and Klebsiella spp.) were more resistant than Gram-positives (Staph. aureus and Streptococcus spp.). Continuous antimicrobial resistance testing and identification of reservoirs of resistance traits in dairy farms are essential to implement proper mitigation measures.